Influence of Cu doping on the visible-light-induced photocatalytic activity of InVO4. Issue 23 (1st March 2017) - Wetchakun, Natda; Wanwaen, Pimonrat; Phanichphant, Sukon; Wetchakun, Khatcharin
Abstract : The photocatalytic degradation of methylene blue (MB) in the presence of pure InVO4 and 0.5–5.0 mol% Cu-doped InVO4 samples under visible light irradiation ( λ ≥ 400 nm) was studied in this research. Abstract : The photocatalytic degradation of methylene blue (MB) in the presence of pure InVO4 or a 0.5–5.0 mol% Cu-doped InVO4 composite under visible light irradiation ( λ ≥ 400 nm) was studied in this research. The structural and photophysical properties of the as-prepared samples in the photocatalytic degradation process were investigated. The doping of InVO4 with a Cu photocatalyst results in wide absorption in the visible-light region and superior visible-light-driven photocatalytic activities in the degradation of MB. The results indicate that the InVO4 sample doped with 1.0 mol% of Cu shows the highest photocatalytic activity. The enhanced photocatalytic activity was attributed to the copper ions acting as trapping sites, facilitating the separation of charge carriers. The main active species for the degradation of MB were investigated to explain the enhancement of the photocatalytic performance of Cu-doped InVO4 . A possible photocatalytic degradation pathway for aqueous MB dye and a charge transfer mechanism for Cu-doped InVO4 were proposed.